Effectiveness of Prenatal Yoga in Reducing Anxiety and Back Pain in Pregnancy: A Systematic Literature Review - Ginting, Ade Krisna (HM Publisher, 2024)
Introduction: Prenatal yoga is a form of exercise that pregnant women can do to improve physical and mental fitness. Several studies have shown that prenatal yoga can reduce anxiety and back pain in pregnancy. This study aims to examine the potential of prenatal yoga in reducing anxiety and back pain in pregnancy through a systematic literature review. Methods: This research was conducted using a systematic literature review method. The articles analyzed were articles published in international scientific journals and in English with the following inclusion criteria: Research conducted on pregnant women in the second or third trimester, Research using prenatal yoga as an intervention, Research using outcome measures for anxiety and/or pain back. Results: Of the 123 articles found, 10 articles met the inclusion criteria and were analyzed. The results showed that prenatal yoga could significantly reduce anxiety (mean difference = -4.20; 95% CI = -6.31, -2.09) and back pain (mean difference = -2.97; 95% CI = -3.96, -2.08) in pregnant women. Conclusion: Prenatal yoga is an effective intervention to reduce anxiety and back pain in pregnancy.